Personalizing Customer Connections: Optimizing CRM Strategies in Levi's Retail Outlet in Ahmedabad city of Gujarat - Pratik Gosiya; Darsh Parekh; Jignesh Vidani (MultiTech Publisher, 2024)
Effective consumer Relationship Management (CRM) is essential in the current competitive retail landscape to comprehensively comprehend consumer requirements, provide tailored experiences, and cultivate loyalty. This research examines the intricacies of customer relationship management (CRM) processes at Levi's retail stores, with the goal of identifying areas of strength, weakness, and providing suggestions to improve the efficacy of CRM. The study employs a qualitative methodology, using purposive sampling to pick Levi's branch managers based on their experience and the importance of their outlets. Interviews are conducted to gather data. Semi-structured interviews provide a thorough investigation of CRM strategy, data management, personalisation efforts, difficulties, and future plans. These interviews are conducted while adhering to ethical rules. Theoretical contributions focus on the actual implementation of CRM ideas, enhancing the current body of knowledge by providing valuable insights into CRM practices that are relevant to the retail industry. The report recommends more investigation into the influence of developing technologies on customer relationship management (CRM) and the analysis of tactics in various retail sectors. To summarise, this study highlights the crucial function of CRM in cultivating customer connections inside Levi's retail stores. The text highlights the significance of technology, personalisation, and customer-centric strategies in attaining retail success via good CRM practices. It offers practical insights for managers and researchers.